Some aspects of the cross-border cooperation development between the Republic of Kazakhstan and the Russian Federation (on the example of neighboring oblasts of Kazakhstan to the Novosibirsk oblast) (International relations and international law Journal, 2018)
The development of cross-border cooperation of States is an important factor in strengthening interstate and international relations, regional development, contributing to their sustainable development and effective integration. Within the framework of the Kazakh-Russian relations cross-border cooperation is an important in terms of strengthening the strategic partnership and integration projects, together with the formation of stable mutually beneficial multi-level ties. Cross-border cooperation of the Novosibirsk region of Russia to Pavlodar, Karaganda, North Kazakhstan and East Kazakhstan region of Kazakhstan has a long history and a high potential for further strengthening in various fields – trade, agriculture, industry, science and education, etc. This aspect of cooperation is very important and in the framework of the Eurasian Economic Union and regional integration as a whole.Key words: cross-border cooperation, Kazakhstan, Russia, the Eurasian integration.